Ta có :
2xy + x - 2y = 4
\(\Rightarrow\) 2y ( x - 1 ) + x = 4
\(\Rightarrow\) 2y ( x - 1 ) + x - 1 = 3
\(\Rightarrow\) 2y ( x - 1 ) + ( x - 1 ) = 3
\(\Rightarrow\) ( x - 1 ) . ( 2y + 1 ) = 3
\(\Rightarrow\) x - 1 và 2y + 1 là Ư(3) = { - 3 ; - 1 ; 1 ; 3 }
Ta có bảng :
x - 1 | - 1 | - 3 | 1 | 3 |
2y + 1 | - 3 | - 1 | 3 | 1 |
x | 0 | - 2 | 2 | 4 |
y | - 2 | - 1 | 1 | 0 |
Vậy ...
2xy+x-2y=4
x(2y+1)-2y=4
x(2y+1)-2y-1=3
x(2y+1)-(2y+1)=3
(x-1)(2y+1)=3
Vì x;y là số nguyên => x-1;2y+1 là số nguyên
=> x-1;2y+1 Ư(3)
Ta có bảng:
x-1 | 1 | 3 | -3 | -1 |
2y+1 | 3 | 1 | -1 | -3 |
x | 2 | 4 | -2 | 0 |
y | 1 | 0 | -1 | -2 |
Vậy cặp số nguyên (x;y) cần tìm là: (2;1) ; (4;0) ; (-2;-1) ; (0;-2).
Ta có : 2xy + x - 2y = 4
2y(x-1) + x - 1 = 3
( x - 1 ) . ( 2y + 1 ) = 3 = 1 . 3
Ta có bảng sau
x - 1 | 1 | 3 | -1 | -3 |
2y + 1 | 3 | 1 | -3 | -1 |
x | 2 | 4 | 0 | -2 |
y | 1 | 0 | -2 | -1 |
Vậy các cặp giá trị ( x ; y ) cần tìm là ( 2 ; 1 ) ; ( 4 ; 0 ) ; ( 0 ; -2 ) ; ( -2 ; -1 )